Breaking the era of energy interdependence in Europe: A multidimensional reframing of energy security, sovereignty, and solidarity - Michael Carnegie LaBelle (Energy Strategy Reviews, 2024)
The era of energy interdependencies between Russia and the European Union (EU) is at an end. This paper advances a nuanced accounting of energy security based on energy sovereignty and energy solidarity. Energy solidarity requires a pooling of energy sovereignty based on values. A historical case study is developed assessing German, Polish, and EU energy relations with Russia. Previous energy security scholarship perceived interdependency as a measurable source of energy security. Since the start of Russia's 2022 war with Ukraine, energy geopolitics has changed, making hard power relevant to Europe's policy toolbox. The EU and Member States responded to Russia's aggression with ‘soft’ policies encouraging the shift away from Russian gas, such as using renewable energy and coordinating joint gas purchases. They also deployed hard power tools in the form of economic sanctions and a Western price cap on Russian oil. Europe regrouped its energy sovereignty and pooled it into energy solidarity, improving its energy security. Both terms are now integral to the EU's energy market operations and are essential in enhancing energy security and developing a new conceptual lens on energy security.